Remnants of a noun class system in Bezen - Kempf, Victoria (AAeO - Afrikanistik-Aegyptologie-Online, 2013)
Bezen looks like a typical Benue-Congo noun class language: A rich variety of prefixes adorn its nouns. Contrary to the linguist’s expectation, the agreement system does not reflect the high number of nominal prefixes but is reduced to four classes: One singular and three plural classes. The function of the nominal prefixes is not restricted to number-marking, however. They also serve to derive a large array of nouns from verbs and adjectives.